Do Good Deeds for the Sake of the Future - Tjiptohadi Sawarjuwono (Green Publisher Indonesia, 2026)
This research explores the concept of continuous good deeds in Islam, emphasizing that such acts are not confined to the month of Ramadan or specific sacred days but are integral to a Muslim’s life. The study aims to analyze the moral and spiritual significance of performing good deeds consistently, as prescribed in the Qur’an and hadith. Utilizing a hermeneutic approach and library research, the paper examines the obligations of ZISWAF (zakat, infaq, sadaqah, and waqf) as key elements in achieving spiritual security and salvation in the hereafter. Through an analysis of various Islamic teachings, this study identifies the essential role of kindness, ethical conduct, and social responsibility in Islam. The findings reveal that good deeds, including small everyday actions such as helping others, speaking kindly, and taking care of animals, are spiritually significant and rewarded by Allah SWT. This study underscores the importance of performing good deeds with sincerity (ikhlas), purely for the sake of Allah’s pleasure, and emphasizes the need for greater awareness regarding Islamic charitable obligations. The research concludes that a life dedicated to doing good, informed by Islamic principles, contributes to a secure future and ultimate peace in the sight of Allah SWT.